Analysis of Governance Diversity and Audit Characteristics on Profitability - Muhammad Taufiq; Devi Fadila (Journal of Applied Accounting and Taxation, 2021)
This study investigates governance diversity-consisting of female members and national diversity in the board of directors and audit characteristics-consisting of quality and audit tenure on profitability with two proxies, return on assets (ROA) and return on equity (ROE). The investigation uses a stewardship theory to explain the effectiveness of the fiduciary relationship between governance and stakeholders. The regression technique uses panel data with 2.151 data from companies listed on the Indonesia Stock Exchange in 2015-2019. This study demonstrates that audit quality has adverse implications for ROA, while other variables have no effect. It`s findings consistent that female members and audit quality reduce fiduciary relationship-meanwhile national diversity and audit tenure do not have any effect on ROE. This study laid to prove the rating of bad corporate governance and suggests to make disruption in corporate governance characteristics.